Between looking and listening: testimonial productions in criminal cases of dance in Irati (1922-1929): (TEL Tempo, Espaço e Linguagem, 2023)
This article aims to investigate the production of testimonies in two prom cases in Irati. The analysis aims to identify the conceptions present in the narratives, which permeate references around those involved in a given conflict. Observing practices, hearing about behaviors and narrating certain versions are the means by which the witnesses enabled mechanisms of influence on a given judicial occasion. The criminal cases in question are components of the Documentation and Memory Center (CEDOC) at Unicentro/Irati, both of which deal with disagreements that took place in rural communities in the municipality, one of which has as its "stage" a "Polish school" in the locality and the other takes place in a "Polish Society" in the community.Keywords:  Irati; Polish ethnicity; Narratives; Dances